Strategy For Application Outsourcing Preparation - Sigit Wijanarko (Institute of Computer Science (IOCS), 2022)
Information systems outsourcing has gained more attention in the last decade. The strategy is meant to relieve some information systems management problems. The scope has improved from data processing and resource sharing to more complex functions e.g. application systems management. Outsourcing penetrations have occurred in functions earlier considered critical and strategic. There have been best practices on managing outsourcing known in industry and acknowledged by the scientific society. Among the important aspects are contract preparation, Service Level Agreement, method of pricing and human resources management. This journal will cover the strategies of outsourcing, which focus on the application systems outsourcing. Among the important goals of outsourcing are the need to focus on the company's core business, achieving cost effectiveness in the application systems management and increasing the service level. Other critical success factors will also be covered e.g. implementation of penalty and incentive mechanism and the anticipation of unexpected conditions.